Down-regulation of vimentin by triorganotin isothiocyanates-nuclear retinoid X receptor agonists: A proteomic approach - Strouhalova, Dana; Macejova, Dana; Mosna, Barbora; Bobal, Pavel; Otevrel, Jan; Lastovickova, Marketa; Brtko, Julius; Bobalova, Janette (Toxicology letters, 2020)
An attempt has been made to delineate the role of natural and synthetic retinoid receptor ligands on vimentin expression in the human triple-negative breast cancer cells. The effects of currently synthesized triorganotin derivatives of the general formula R3SnX (R is butyl or phenyl, X is isothiocyanate), which are considered RXR ligands, were investigated in the human MDA-MB-231 breast cancer cell line. Studies were evaluated in the presence and absence of all-trans retinoic acid (ATRA), a natural RAR ligand. Vimentin represents the major protein associated with epithelial-mesenchymal transition (EMT), an essential process when the primary tumour transforms into a malignant one. mRNA and proteomic data obtained in this study, based on the PDQuest software protein evaluation and further quantification of proteins by iTRAQ analysis, suggest that vimentin was significantly reduced in the combination of RAR ligand and RXR ligand treatment. Both tested triorganotin compounds showed similarly reduced expression of vimentin, but tributyltin isothiocyanate (TBT-ITC) proved to be more effective than triphenyltin isothiocyanate (TPT-ITC). Furthermore, the effect of natural (9cRA) and synthetic RXR ligands, both chloride and isothiocyanate derivatives, on vimentin expression was compared.
Keywords: nádorové buněčné linie; Signal Transduction; epitelo-mezenchymální tranzice; Trialkyltin Compounds; spektrometrie hmotnostní - ionizace laserem za účasti matrice; tandemová hmotnostní spektrometrie; Vimentin; vimentin; lidé; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Cell Line, Tumor; Proteomics; down regulace; nádory prsu; 2D gelová elektroforéza; Electrophoresis, Gel, Two-Dimensional; Epithelial-Mesenchymal Transition; Female; Organotin Compounds; trialkylcínové sloučeniny; Antineoplastic Agents; Tretinoin; Retinoid X Receptors; Tandem Mass Spectrometry; Breast Neoplasms; retinoidní X receptory; ženské pohlaví; proteomika; Down-Regulation; Humans; organocínové sloučeniny; signální transdukce; protinádorové látky; tretinoin